2017
DOI: 10.1080/0284186x.2016.1275780
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave among parents of children with cancer – a national cohort study

Abstract: Findings confirm that mothers and fathers of children diagnosed with cancer are at higher risk of sickness absence from work, with particularly pronounced risk among bereaved parents. Acquisition of further knowledge is warranted regarding possibilities and constraints of parents trying to combine their work life with caring for both their child and themselves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 17 publications
(28 reference statements)
4
22
2
2
Order By: Relevance
“…Thus, even after treatment completion, parents, in particular mothers, are at an increased risk of fatigue symptoms, posttraumatic stress, and psychiatric disorders . Psychological distress and feelings of uncertainty, helplessness, and loneliness may compromise health and increase disease risk . Limited participation in work during periods spent caring for children also may lead to the loss of personal satisfaction, social networks, and possibly respite from home and care responsibilities, which also may damage health …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, even after treatment completion, parents, in particular mothers, are at an increased risk of fatigue symptoms, posttraumatic stress, and psychiatric disorders . Psychological distress and feelings of uncertainty, helplessness, and loneliness may compromise health and increase disease risk . Limited participation in work during periods spent caring for children also may lead to the loss of personal satisfaction, social networks, and possibly respite from home and care responsibilities, which also may damage health …”
Section: Discussionmentioning
confidence: 99%
“…30 Psychological distress and feelings of uncertainty, helplessness, and loneliness 31 may compromise health and increase disease risk. 32,33 Limited participation in work during periods spent caring for children also may lead to the loss of personal satisfaction, social networks, and possibly respite from home and care responsibilities, which also may damage health. 34 The income derived from work and total income were found to be persistently lower for the mothers of children with cancer compared with reference mothers after approximately 3 years, but such differences were not observed in fathers.…”
Section: Income and Social Benefits Trajectories/hiyoshi Et Almentioning
confidence: 99%
“…We identified 3359 articles through literature searches and included 35 articles, reporting on 29 individual studies (Figure ). Thirteen (37%) studies were conducted in Europe, 16 (46%) in North America/Australia, and six (17%) in Asia/Africa (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Two US studies reported that more than 50% of parents used individual fundraising as a financial coping strategy . In Sweden, parents of children with cancer were more likely to rely on sickness or childcare benefits than comparison parents . Sick leave was more often used by mothers than fathers .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation